History, power, text : cultural studies and Indigenous studies - Neale, Timothy; McKinnon, Crystal; Vincent, Eve (CSR books ;, 2014)
"History, power, text: cultural studies and Indigenous studies is a collection of essays on Indigenous themes published between 1996 and 2013 in the journal known first as UTS review and now as Cultural studies review. This journal opened up a space for new kinds of politics, new styles of writing and new modes of interdisciplinary engagement. History, power, text highlights the significance of just one of the exciting interdisciplinary spaces, or meeting points, the journal enabled. 'Indigenous cultural studies' is our name for the intersection of cultural studies and Indigenous studies showcased here."--Publisher's website.